Edges of Financial Literacy in Business Competitiveness - Castañeda Acuña, Elsa Roxana; Sinforoso Martínez, Saulo (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2023)
Currently, organizations must strengthen their competitive advantages to respond to the changes imposed by globalization. Financial literacy is related to competitiveness. However, it is a subject little addressed in the organizational field and poses dilemmas to be strengthened. OBJECTIVE: To analyze properties, gaps and implications of financial literacy and organizational competitiveness to specify this relationship. MATERIAL AND METHOD: An analysis was carried out using the qualitative technique of grounded theory. First, 44 academic texts on competitiveness and financial literacy were reviewed, obtained from the databases of: JSTOR; Ebsco, Wiley, Science direct, Dialnet, google academic, Flacso and Scielo; to later classify, order and obtain analysis categories to analyze properties, gaps and implications between both constructs. RESULTS: Most of the studies focus on financial elements and administrative processes, positively associated with obtaining returns; efficiency in financial performance; venture sustainability; technological adaptation, among others. CONCLUSIONS: Financial literacy strengthens organizational functions that are necessary for the development of competitive advantages. However, the theoretical review yields different implications on the conceptual and methodological scope of financial literacy, due to the different perceptions of financial knowledge and its application.